Method for synergistically improving seepage and corrosion resistance of loess through MICP-biogel
Through the method of MICP-biogel collaboratively improving loess, the problems of uneven distribution and brittleness of precipitates in loess curing are solved, and uniform curing of loess and anti-seepage corrosion resistance are improved, forming a high-strength and low-permeability curing layer, reducing costs and simplifying the process.
Patent Information
- Application Number
- CN202510501190.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-21
- Publication Date
- 2025-06-03
AI Technical Summary
When MICP technology cures loess, the precipitates are unevenly distributed and have high brittleness, which leads to obvious anisotropy characteristics of the reinforced soil, which is more difficult to use alone.
The method of synergistically improving loess by MICP-biogels is adopted to form a gel material by mixing the biogel with loess powder, and then using MICP technology to improve loess, combined with the protection effect of the biogel, the anti-seepage resistance of loess is improved.
The uniform curing of loess and the improvement of anti-seepage corrosion resistance are achieved, and a high-strength and low-permeability cured layer is formed, reducing costs and simplifying the process.
Smart Images

Figure CN120083224A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of slope protection, and particularly relates to a method for synergistically improving the anti-seepage and anti-erosion properties of loess by using MICP-bio-gel. Background Technique
[0002] Loess has well-developed vertical joints and strong collapsibility and water sensitivity. Slope diseases caused by rainwater are common engineering challenges in the Loess Plateau region. On the one hand, rainfall increases the soil moisture content and reduces the matrix suction, thereby reducing the strength of loess and leading to slope deformation and instability. On the other hand, due to the generally large slope and low vegetation coverage of loess slopes, short-term heavy rainfall easily saturates the shallow soil of the slope quickly, triggering surface runoff and resulting in slope erosion. These slope diseases seriously hinder the regional social and economic development.
[0003] Currently, in the field of loess slope protection technology, geotechnical protection (concrete retaining wall), ecological protection (three-dimensional net grass planting) and soil solidification slope protection technology (polymer solidifying agent) are still mainly adopted. The main advantages of the above technologies are that they can effectively enhance the slope stability. However, these traditional improvement measures have problems such as high cost, cumbersome and time-consuming processes, poor durability of materials or potential environmental risks.
[0004] In recent years, the MICP (Microbial-induced carbonate precipitation) technology has shown unique advantages as a new method for enhancing geological structures using microorganisms. This technology uses the vital activities of microorganisms to induce calcium carbonate precipitation, generating a large amount of calcium carbonate precipitate, filling the intergranular gaps, cementing soil particles into aggregates, improving the physical and chemical properties of the soil, and realizing soil solidification. The MICP technology is currently considered an effective method for improving the properties of sandy soil, and there are relatively few studies on using it to solidify loess. The main reason is that the large porosity and well-developed vertical joints of loess make the differential penetration of the bacterial solution used in the MICP process, and the distribution of the precipitates generated by mineralization is uneven. At the same time, due to the brittleness of the precipitates, the anisotropic characteristics of the reinforced soil mass are obvious; it is relatively difficult to use the MICP technology alone to protect loess slopes. Currently, the MICP technology is often combined with auxiliary materials (polyacrylamide, polyvinyl acetate) to improve the cementing effect, but these auxiliary materials have certain negative impacts on the environment. Summary of the Invention
[0005] Aiming at the problems of uneven distribution of precipitates generated during the solidification of loess by the current MICP technology and obvious anisotropic characteristics of the reinforced soil mass due to the brittleness of the precipitates, the invention provides an environmentally friendly, non-toxic and harmless, simple process, low-cost, convenient construction, and large-area applicable method for synergistically improving the anti-seepage and anti-erosion properties of loess by using the MICP-bio-gel.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for improving the anti-seepage and anti-erosion of loess by MICP-bio-gel synergy. After improving the surface of loess with bio-gel material, the MICP technology is used to improve the loess. The specific steps are as follows:
[0008] Step 1, preparation of gel material: Mix bio-gel and loess powder evenly to obtain the gel material;
[0009] Step 2, preparation of mineralizing bacterial solution: Activate the mineralizing bacterial strain and prepare the mineralizing bacterial solution and its cementing solution;
[0010] Step 3, slope treatment: Clean the weeds on the slope and carry out scraping treatment. After the scraping treatment, wet the slope;
[0011] Step 4, dry powder spraying: Evenly spray the gel material onto the slope after scraping treatment. After spraying, carry out mechanical compaction;
[0012] Step 5, bacterial solution spraying: Mix the mineralizing bacterial solution and its cementing solution evenly and immediately spray it onto the slope after compaction treatment;
[0013] Step 6: Cover with a film and cure for three days until the reaction ends.
[0014] Furthermore, in the step 1, the bio-gel material is powdery sesbania gum; the specific parameters of the sesbania gum are: mesh number ≤ 150; viscosity is 1.5 - 1.6 Pa·s; PH value is 7. The present invention uses sesbania gum, the loess at the construction site, and the in-situ bacterial strain as the main raw materials. Sesbania gum is a natural plant gum extracted from plant seeds. It can dissolve in water at room temperature and form a hydrocolloid with a very high viscosity, showing a viscous state. Its viscosity is higher than that of most bio-gels; it is stable within the range of PH 6 - 8 and has the highest viscosity at a PH value of 7. It is a sustainable and renewable carbon-neutral material and is suitable for the protection of weakly alkaline loess slopes in the northwest region.
[0015] Furthermore, in the step 1, the volume ratio of the bio-gel to the loess powder is 3 - 7:50. The dry mixing method is used for stirring: that is, all the materials used are dry powders and are mixed evenly before use. This mixing method can obtain a huge and uniform distribution of biopolymers, making the performance of the anti-seepage layer evenly distributed.
[0016] Furthermore, in the step 2, the mineralizing bacterial strain selected is Sporosarcina pasteurii.
[0017] Further, the specific method for activating the mineralizing bacteria strains and preparing the mineralizing bacteria liquid and its cementing liquid in Step 2 is as follows: Place the liquid medium in an autoclave and sterilize it for 3 h, followed by aseptic inoculation; Place the mixed liquid containing a single strain in a speed-adjustable oscillator and culture it at a rotation speed of 150 r / min for 24 h; Use an ultraviolet spectrophotometer to measure the optical density value OD600 of the bacteria liquid and maintain OD600 = 0.6.
[0018] Further, the medium is a selective medium with guar gum as the sole carbon source; The specific components of the selective medium are: Guar gum: 10 g / L (carbon source); Yeast extract: 5 g / L (nitrogen source and other nutrients); Peptone: 5 g / L (nitrogen source); Phosphate buffer: 2.5 g / L (providing inorganic salts and pH buffering); Agar: 15 - 20 g / L (as a coagulant); Bromothymol blue: 0.05 g / L (as a pH indicator).
[0019] Further, the ratio of the cementing liquid in Step 2 is 1.0 mol / L of calcium chloride and 1.0 mol / L of urea; The cementing liquid is prepared with deionized water.
[0020] Further, the spraying amount of the gel material in Step 4 is 1 - 2 kg / m 3 .
[0021] Further, the spraying amount of the bacteria liquid in Step 5 is 1.5 - 1.8 L / m 2 ; The volume ratio of the addition amount of the cementing liquid to the bacteria liquid is 1:1.
[0022] Compared with the prior art, the present invention has the following advantages:
[0023] Create a favorable microenvironment: The biogel provides an ideal microenvironment for microorganisms, including suitable pH, temperature, and essential nutrients, creating favorable conditions for the growth and activities of microorganisms.
[0024] Protect and fix microorganisms: The biogel has good viscosity and stability, can effectively fix and protect microorganisms, enabling them to survive and reproduce in harsh environments and maintaining their mineralization activity.
[0025] Enrich nutrients: The biogel can adsorb and enrich nutrients, providing sufficient nutrients for microorganisms, so that they can carry out metabolic activities more effectively and accelerate the mineralization process of mineralizing bacteria.
[0026] Improve the stability of the protective layer: Through intensive scraping treatment, the contact area between the anti-seepage material and the loess slope is significantly increased, and due to the dense wedge-shaped grooves generated by scraping, the anti-seepage material fits well with the grooves, and no large-area shedding will occur after the formation of the anti-seepage layer, largely ensuring the stability of the protective layer.
[0027] Promote metabolite accumulation: Protected by the biogel, the metabolites produced by microorganisms can accumulate in a local area, increasing the Ca 2+ utilization rate, thereby promoting the mineralization reaction, increasing the calcium carbonate content in the upper and middle parts of the specimen, and improving the forming effect.
[0028] Provide a mineralization template: The structure of the biogel can serve as a nucleation site for crystal growth during the mineralization process, promoting the formation of a more regular and stable mineral structure.
[0029] Regulate the local pH: The metabolic activities of biomineralization bacteria inside the biogel may affect the local pH, creating a more optimal acid-base environment for the mineralization process.
[0030] Enhance the toughness of the mineralized layer: Through the water retention capacity, controllable pore structure, and flexible cross-linking mechanical properties of the biogel, it can promote more uniform calcium carbonate deposition, increase the internal structural uniformity of the mineralized layer, and enhance the overall toughness of the mineralized layer.
[0031] The method of the present invention utilizes the MICP technology to integrate biogel and biomineralization bacteria, enhancing the anti-seepage and anti-corrosion performance of loess slopes, and providing an efficient and environmentally friendly new protection solution for loess slopes. On the one hand, biogels generally have the characteristics of environmental friendliness; on the other hand, appropriate biogels can improve the mineralization rate and mineral product yield of biomineralization bacteria. At the same time, since the biogel is a flexible macromolecular material, the mineralized precipitate formed with the biogel as the environment has similar characteristics to the natural loess cement, thereby effectively improving the isotropy of the reinforced soil mass and enhancing the anti-seepage and anti-corrosion performance of the loess slope. Description of the Drawings
[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following will briefly introduce the drawings required for the description of the embodiments. Obviously, the drawings in the following description are only some embodiments of the present application. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.
[0033] Figure 1 It is a schematic diagram of the technical route of the present invention;
[0034] Figure 2 It is a scanning electron microscope (SEM) picture (magnification: 200 times) of the loess specimen improved by the MICP technology in Example 1;
[0035] Figure 3 It is a scanning electron microscope (SEM) picture (magnification: 500 times) of the loess specimen improved by the MICP technology in Example 1;
[0036] Figure 4 It is the scanning electron microscope (SEM) image (magnification: 3000 times) of the loess specimen improved by the MICP technology in Example 1;
[0037] Figure 5 It is the scanning electron microscope (SEM) image (magnification: 200 times) of the loess specimen improved by the synergistic effect of the MICP technology and sesbania gum in Example 2;
[0038] Figure 6 It is the scanning electron microscope (SEM) image (magnification: 500 times) of the loess specimen improved by the synergistic effect of the MICP technology and sesbania gum in Example 2;
[0039] Figure 7 It is the scanning electron microscope (SEM) image (magnification: 3000 times) of the loess specimen improved by the synergistic effect of the MICP technology and sesbania gum in Example 2;
[0040] Figure 8 The broken line graph of the change in the permeability coefficient (cm·s -1 ) of the loess specimen improved by the MICP technology in Example 1;
[0041] Figure 9 The broken line graph of the change in the permeability coefficient (cm·s -1 ) of the loess specimen improved by the synergistic effect of the MICP technology and sesbania gum in Example 2;
[0042] Figure 10 It is the broken line graph of the change in the surface hardness (HD) of the loess specimen improved by the MICP technology in Example 1;
[0043] Figure 11 It is the broken line graph of the change in the surface hardness (HD) of the loess specimen improved by the synergistic effect of the MICP technology and sesbania gum in Example 2. Detailed implementation manners
[0044] To deeply understand the present invention, we will describe it comprehensively and meticulously. However, the present invention has various implementation manners and is not limited to the specific examples listed herein. The presentation of these examples aims to deepen the comprehensive understanding of the disclosed content of the present invention.
[0045] Example 1: Improving the loess specimen with the MICP technology
[0046] Step 1: Activate and enrich the mineralizing bacteria. First, according to the physiological characteristics of the mineralizing bacteria, a selective medium is designed, and the specific components are: 10 g / L of sesbania gum (carbon source); 5 g / L of yeast extract (nitrogen source and other nutrients); 5 g / L of peptone (nitrogen source); 2.5 g / L of phosphate buffer solution (providing inorganic salts and pH buffering); 15 - 20 g / L of agar (as a coagulant); 0.05 g / L of bromothymol blue (as a pH indicator). The liquid medium is sterilized in an autoclave for 3 h, and then inoculated in a sterile laboratory. After inoculation, the mixture containing a single strain (Sporosarcina pasteurii) is placed in a variable-speed oscillator and cultured at a rotation speed of 150 r / min for 24 h. The optical density value OD600 of the bacterial solution is measured using an ultraviolet spectrophotometer, and the OD600 of the bacterial solution is maintained at 0.6.
[0047] Step 2: Prepare the cementing solution. The cementing solution is prepared according to the ratio of calcium chloride:urea = 1:1 and the nutrient = broth 3 mol / L. Five groups of cementing solutions with calcium chloride concentrations of 0.25 mol / L, 0.5 mol / L, 1 mol / L, 1.5 mol / L, and 3 mol / L are prepared, and the solvent is ionized water.
[0048] Step 3: Prepare the remolded loess core cutter specimen. According to the core cutter size Ф61.8 mm×H40 mm, it is compacted once using a static pressure loading device, with a water content of 8% and a dry density of 1.4 g / cm 3 of the remolded soil core cutter specimen. Two groups of specimens are prepared. The surface of the prepared core cutter specimen is roughened, and the roughening depth is required to be maintained at 0.5 mm - 2 mm, and the width is maintained at 1 mm - 2 mm.
[0049] Step 4: Spray the mineralizing bacteria. Use a sprayer to evenly spray the high-concentration bacterial solution prepared in 1) on the surface after 3) treatment at a spraying rate of 0.5 - 0.6 L / m 2 . After the bacterial solution is completely infiltrated, spray the cementing solution prepared in 2). Among them, the spraying amount of the cementing solution is 1:1 with the spraying amount of the bacterial solution.
[0050] Step 5: Cure the specimen. Put the prepared specimen into a thermostatic and humid test chamber for curing until the reaction is complete. The curing temperature is set at 25°C and the humidity is 95%. The curing days are 1 d, 3 d, 7 d, and 14 d respectively. In this example, the permeability coefficient and surface hardness of the cured loess core cutter specimen are tested, and the test results are as Figure 8 、 Figure 10 shown. Its SEM images are as Figure 2 、 Figure 3 、 Figure 4 shown.
[0051] Example 2: MICP-bio-gel collaborative improvement of loess specimens
[0052] 1) Preparation of gel material. Take a certain amount of 0.5 mm loess powder, add 10% by mass of sesbania gum powder, mix evenly dry, and let it stand for later use.
[0053] 2) Activation and enrichment culture of mineralizing bacteria. First, according to the physiological characteristics of mineralizing bacteria, design a selective medium for microbial enrichment culture and targeted screening. The medium used is a selective medium with sesbania gum as the sole carbon source. The specific components are: sesbania gum 10 g / L (carbon source); yeast extract 5 g / L (nitrogen source and other nutrients); peptone 5 g / L (nitrogen source); phosphate buffer 2.5 g / L (providing inorganic salts and pH buffering); agar 15 - 20 g / L (as a coagulant); bromothymol blue 0.05 g / L (as a pH indicator). Sterilize the liquid medium in an autoclave for 3 h, and then inoculate it in a sterile laboratory. After inoculation, place the mixture containing a single strain (Sporosarcina pasteurii) in a variable-speed oscillator and culture it at a rotation speed of 150 r / min for 24 h. Use an ultraviolet spectrophotometer to measure the optical density value OD600 of the bacterial solution, and keep the OD600 of the bacterial solution = 0.6.
[0054] 3) Preparation of cementing liquid. The cementing liquid concentration is prepared according to calcium chloride∶urea = 1∶1 and nutrient = broth 3 mol / L. Prepare five groups of cementing liquids with calcium chloride concentrations of 0.25 mol / L, 0.5 mol / L, 1 mol / L, 1.5 mol / L, and 3 mol / L, and the solvent is ionized water.
[0055] 4) Preparation of remolded loess core cutter specimen. According to the core cutter size Ф61.8 mm×H40 mm, use a static pressure loading device to compact it once, configure the water content to be 8%, and prepare a remolded soil core cutter specimen with a dry density of 1.4 g / cm 3 ³. Scrape the surface of the prepared core cutter specimen. The scraping depth requirement is to keep it at 0.5 mm - 2 mm, and the width is kept at 1 mm - 2 mm.
[0056] 5) Coating of gel material. Wet the surface of the scraped specimen, and spray the material prepared in 1) on the surface. The spraying thickness is 0.5 - 2.5 mm, and the spraying amount is 1 - 2 kg / m 3 ². After spraying, use a static pressure loading device to re-press it to the original compaction degree. The spraying amount during the preparation process is the same as the scraping removal amount, so that the water content and dry density of the specimen remain unchanged before and after treatment.
[0057] 6) Spraying of mineralizing bacteria. Use a spray bottle to spray on the surface after the treatment in 4) at 1.5 - 1.8 L / m 2Spray the high-concentration bacterial solution prepared and cultured in 2) evenly at the spraying volume, and after the bacterial solution is completely infiltrated, spray the cementing solution prepared in 3). Among them, the spraying volume of the cementing solution is kept consistent with the spraying volume of the bacterial solution.
[0058] 7) Specimen curing. Put the prepared specimen into a thermostatic and humid test chamber for curing until the reaction is complete. The curing temperature is set at 25 °C and the humidity is 95%. The curing days are 1d, 3d, 7d, and 14d respectively.
[0059] In this embodiment, the permeability coefficient and surface hardness of the loess core sample after curing are tested, and the test results are as Figure 9 、 Figure 11 shown. Its SEM images are as Figure 5 、 Figure 6 、 Figure 7 shown.
[0060] In summary, for the loess specimen treated by the present invention, a flat, high-strength and low-permeability solidified layer will be formed on its surface. When the concentration of the cementing solution is 1 mol / L, the surface hardness of the specimen cured for 14 days is increased by 238% compared with the loess specimen treated by the single MICP technology; the permeability coefficient is reduced by about two orders of magnitude compared with the loess specimen treated by the MICP technology. The preparation method and usage method of the anti-seepage material of the present invention are very convenient, which can make the operation of the anti-seepage layer in later maintenance simple, with low cost, low consumption and high efficiency.
[0061] The content not detailedly described in the specification of the present invention belongs to the prior art well-known to those skilled in the art. Although the illustrative specific embodiments of the present invention are described above for the understanding of those skilled in the art in this technical field, it should be clear that the present invention is not limited to the scope of the specific embodiments. For those of ordinary skill in this technical field, as long as various changes are within the spirit and scope of the present invention defined and determined by the appended claims, these changes are obvious, and all inventions and creations using the concept of the present invention are within the scope of protection.
Claims
1. A method for improving loess anti-seepage and anti-corrosion by MICP-biogel synergistically, characterized in that: The following steps are involved: Step 1, preparation of gel material: mixing the biogel and loess powder evenly to obtain a gel material; Step 2, preparation of mineralized bacterial solution: activating the mineralized bacterial strains, preparing the mineralized bacterial solution and its cementing solution; Step 3, slope surface treatment: clean the weeds on the slope and scrape it, and wet the slope after scraping; Step 4, dry powder spraying: spray the gel material evenly onto the scraped slope surface, and perform mechanical compaction after spraying; Step 5, bacterial liquid spraying: evenly mix the mineralized bacterial liquid and its binder liquid, and immediately spray them onto the slope surface after compaction.
2. The method for improving loess anti-seepage and anti-corrosion by MICP-biogel synergistically according to claim 1, characterized in that: The biogel material in step 1 is powdered sesbania gum; the specific parameters of the sesbania gum are: mesh size ≤ 150; viscosity 1.5-1.6 Pa·s; pH value 7.
3. The method for improving loess anti-seepage and anti-corrosion by MICP-biogel synergistically according to claim 1, characterized in that: In the step 1, the volume ratio of the biogel to the loess powder is 3 to 7:
50.
4. The method for improving loess anti-seepage and anti-corrosion by MICP-biogel synergistically according to claim 1, characterized in that: In the step 2, the mineralizing bacteria species is selected from Sporosarcina pasteurii.
5. The method for improving loess anti-seepage and anti-corrosion by MICP-biogel synergistically according to claim 2, characterized in that: The specific method for activating the mineralizing bacteria strains and preparing the mineralizing bacteria liquid and its cementing liquid in the step 2 is: sterilizing the liquid culture medium in a high pressure sterilizer for 3 hours, and then aseptically inoculating; placing the mixed liquid containing a single bacterial strain in a speed-adjustable oscillator, and culturing it at a speed of 150r / min for 24 hours; using an ultraviolet spectrophotometer to test the optical density value OD600 of the bacterial liquid, and maintaining OD600=0.
6.
6. The method for improving loess anti-seepage and anti-corrosion by MICP-biogel synergistically according to claim 5, characterized in that: The culture medium is a selective culture medium with sesbania gum as the sole carbon source; the specific components of the selective culture medium are: sesbania gum: 10 g / L; yeast extract: 5 g / L; peptone: 5 g / L; Phosphate buffer: 2.5 g / L; Agar: 15-20 g / L; Bromothymol blue: 0.05 g / L.
7. The method for improving loess anti-seepage and anti-corrosion by MICP-biogel synergistically according to claim 2, characterized in that: The ratio of the binder in step 2 is 1.0 mol / L calcium chloride and 1.0 mol / L urea; the binder is prepared with deionized water.
8. The method for improving loess anti-seepage and anti-corrosion by MICP-biogel synergistically according to claim 2, characterized in that: The spraying amount of gel material in step 4 is 1-2 kg / m 3 .
9. The method for improving loess anti-seepage and anti-corrosion by MICP-biogel synergistically according to claim 2, characterized in that: The spraying amount of the bacterial solution in step 5 is 1.5 to 1.8 L / m 2 ; The volume ratio of the binder added to the bacterial solution is 1:1.
Citation Information
Cited By
Preparation and construction method of vegetation macroporous material for spraying and covering bare and steep rock surface
CN120770313A
Rare earth ore stope bottom W-shaped liquid collecting structure manufacturing method based on biotechnology
CN121228032A